Inhibitory control and visuospatial working memory contribute to 5-year-old children's use of quantitative inversion. (February 2023) - Ching, Boby Ho-Hong
Abstract: This study examined the hypothesis that general cognitive resources moderated 5-year-old children's performance differences between the Concrete Identical and the Pure Quantity conditions on inversion problems (a + b – b) but not on standard problems (a + b – c). Study 1 ( N = 104) showed that children who experienced higher visuospatial working memory burden performed significantly poorer in solving the inversion problems in the Pure Quantity condition than in the Concrete Identical condition, whereas those who experienced lower working memory burden showed no such difference. Study 2 ( N = 194) demonstrated that children with lower levels of inhibitory control solved significantly fewer inversion problems in the Pure Quantity condition than in the Concrete Identical condition, whereas no such difference was found in children with higher levels of inhibitory control. These findings suggest that inhibitory control and visuospatial working memory may support children's use of quantitative inversion. Highlights: Five-year-old children can reason about quantitative inversion. Visuospatial working memory affected children's performance in inversion problems. Inhibitory control affected children's performance in inversion problems.